Arabic Language Teachers’ Strategies to Improve Students’ Reading Skills at an Islamic Junior High School in Lombok, Indonesia - Siska Wahyu Puji Lestari; Yusraini; Irfan; Mustar; Muhammad Ahmad Abdul Ghofar Ahmad; Mursyid (Al-Muyassar: Journal of Arabic Education, 2026)
The learning strategies implemented by teachers play a crucial role in improving students' reading skills (mahārah qirā'ah) in Arabic language learning. However, empirical studies on teachers' strategies applied contextually in regional madrasahs with limited learning facilities remain relatively scarce. This study aims to describe and analyze the strategies of Arabic language teachers in improving students' mahārah qirā'ah at MTs Babul Mujahidin, Bayan Village, North Lombok, West Nusa Tenggara. The study employed a descriptive qualitative approach involving one Arabic language teacher as the main informant and three students as supporting informants, selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The findings show that the teacher applied a direct-practice-based learning strategy (mubāsyarah) through reading modeling, repeated reading, imitation of the teacher's reading, individual reading practice, vocabulary reinforcement, and simple conversation practice. These strategies contributed to improved reading accuracy, self-confidence, active participation, and basic comprehension of Arabic texts, despite persisting challenges such as limited learning media, students' low initial reading ability, and minimal support from the learning environment. The novelty of this study lies in its analysis of Arabic teachers' learning strategies developed contextually in accordance with the characteristics of regional madrasahs with limited facilities. The findings contribute theoretically to the development of studies on mahārah qirā'ah learning strategies and offer practical recommendations for teachers and madrasah administrators in designing more adaptive, systematic, and sustainable Arabic reading instruction